Pengaruh Pembelajaran Deepdialogue/Critical Thinking (DD/CT) Terhadap Kemampuan Penalaran Matematis Siswa Pada Materi Peluang Di Kelas X SMAS Katolik Budi Murni – 3 Medan - Pasaribu, Ruth Ester Maria; Pangaribuan, Lena R.; Naibaho, Tutiarny (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
This study was conducted to determine the influence of a deep dialogue / critical thinking (DD/CT) learning model on the mathematical reasoning ability of students in class X of high school on opportunity materials at Budi Murni Catholic Private High School – 3 Medan. The type of research used is quantitative using quasi-experimentation with the research design being pretest postest control group design. This study uses 2 classes, namely the control class and the experimental class. The test of the research instruments used in this study are the validity test, reliability test, question differentiating power test and question difficulty level test, to find out whether the question to be tested is feasible or not. The prerequisite tests used are the normality test and the homogeneity test. For the hypothesis test, a t-independent test (α:0.05%) was used with the P criterion. The value must be less than 0.05, so there is a significant difference. The result of the t- independent test obtained was 0.004. The significant difference between the control class and the experimental class that was given different treatment can be concluded that the deep dialogue/critical thinking (DD/CT) learning model has an effect on students' mathematical reasoning skills.